RELATIONSHIP LEVEL OF PARENTAL KNOWLEDGE ABOUT THE FUNCTION OF PLAYING WITH THE PROVISION OF APE (EDUCATIONAL GAME TOOLS) CHILDREN AGED 4-6 YEARS IN BALONG TUNJUNG VILLAGE, BENJENG DISTRICT, GRESIK - Sulpat, Emuliana; Listianingsih, Fitria (Journal of Vocational Nursing, 2021)
Introduction: Play is an activity where the child can perform or practice skills, express thoughts, be creative, prepare to play and behave maturely, the results of a preliminary study in Benjeng 50 parental (64.70%) do not know the function of play for children. The research objective is to determine the relationship between the level of parental knowledge and the provision of APE. Methods: The design of this study was a correlation study with a Cross Sectional approach, with all parent populations of 34 respondents, a sample of 20 respondents.  Sampling using simple random sampling technique, data taken using questionnaire and observation sheets, then analyzed by spearman test with a significance level a α = 0.05. Results: The results showed that (50%) of respondents had a moderate level of knowledge about the function of play and (65%) respondents gave APE. The statistical test result obtained rs = 0,499 and p= 0,025, where p> 0,05. Conclusion: This study is a relationship between the level of knowledge of parents about the function of play and the provision of APE,  in Balong Tunjung Village, Benjeng  , Gresik.